Corticosterone Induces Rapid Spinogenesis via Synaptic Glucocorticoid Receptors and Kinase Networks in Hippocampus - Komatsuzaki, Yoshimasa; Hatanaka, Yusuke; Murakami, Gen; Mukai, Hideo; Hojo, Yasushi; Saito, Minoru; Kimoto, Tetsuya; Kawato, Suguru (PLOS ONE, 2012)
Background Modulation of dendritic spines under acute stress is attracting much attention. Exposure to acute stress induces corticosterone (CORT) secretion from the adrenal cortex, resulting in rapid increase of CORT levels in plasma and the hippocampus. Methodology/Principal Findings Here we demonstrated the mechanisms of rapid effect (∼1 h) of CORT on the density and morphology of spines by imaging neurons in adult male rat hippocampal slices. The application of CORT at 100–1000 nM induced a rapid increase in the density of spines of CA1 pyramidal neurons. The density of small-head spines (0.2–0.4 µm) was increased even at low CORT levels (100–200 nM). The density of middle-head spines (0.4–0.5 µm) was increased at high CORT levels between 400–1000 nM. The density of large-head spines (0.5–1.0 µm) was increased only at 1000 nM CORT. Co-administration of RU486, an antagonist of glucocorticoid receptor (GR), abolished the effect of CORT. Blocking a single kinase, such as MAPK, PKA, PKC or PI3K, suppressed CORT-induced enhancement of spinogenesis. Blocking NMDA receptors suppressed the CORT effect. Conclusions/Significance These results imply that stress levels of CORT (100–1000 nM) drive the spinogenesis via synaptic GR and multiple kinase pathways.